Conductance Artery Wall Layers and Their Respective Roles in the Clearance Functions. Issue 9 (4th August 2022) - Michel, Jean-Baptiste; Lagrange, Jeremy; Regnault, Veronique; Lacolley, Patrick
Abstract : Evolutionary organization of the arterial wall into layers occurred concomitantly with the emergence of a highly muscularized, pressurized arterial system that facilitates outward hydraulic conductance and mass transport of soluble substances across the arterial wall. Although colliding circulating cells disperse potential energy within the arterial wall, the different layers counteract this effect: (1) the endothelium ensures a partial barrier function; (2) the media comprises smooth muscle cells capable of endocytosis/phagocytosis; (3) the outer adventitia and perivascular adipocytic tissue are the final receptacles of convected substances. While the endothelium forms a physical and a biochemical barrier, the medial layer is avascular, relying on the specific permeability properties of the endothelium for metabolic support. Different components of the media interact with convected molecules: medial smooth muscle cells take up numerous molecules via scavenger receptors and are capable of phagocytosis of macro/micro particles. The outer layers—the highly microvascularized innervated adventitia and perivascular adipose tissue—are also involved in the clearance functions of the media: the adventitia is the seat of immune response development, inward angiogenesis, macromolecular lymphatic drainage, and neuronal stimulation. Consequently, the clearance functions of the arterial wall are physiologically essential, but also may favor the development of arterial wall pathologies. This review describes how the walls of large conductance arteries have acquired physiological clearance functions, how this is determined by the attributes of the endothelial barrier, governed by endocytic and phagocytic capacities of smooth muscle cells, impacting adventitial functions, and the role of these clearance functions in arterial wall diseases.